Physico-chemical characterization of 'BRS Hozan' and 'Roxo Pérola de Caçador' garlic as a function of storage time - Bessa, Antonia Tamires Monteiro; Lopes, Welder de Araújo Rangel; Silva, Otaciana Maria dos Prazeres da; Lima, Mayky Francley Pereira de; Oliveira, Pedro Ramon Holanda de; Sousa, Hiago Costa de; Aguiar, Adriano Fontes; Negreiros, Maria Zuleide de (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2018)
Post-harvest storage can be a useful instrument for garlic producers to provide good quality produce with affordable prices for consumers. Thus, the objective of this study was to evaluate the changes in the physicochemical characteristics of common and noble garlic during storage under environmental conditions. The treatments were distributed in split plots; the plots were defined by the garlic cultivars: ‘BRS Hozan’ and ‘Roxo Pérola de Caçador’, and the storage times: 0, 30, 60, 90 and 120 days. A randomized block design was used, with four replications. We evaluated the weight loss, pith index, soluble solids, titratable acidity, pH, soluble solids/ titratable acidity, pungency, total solids and industrial index. For storage time, there was an increase in the weight loss, chopping index and titratable acidity, as well as a reduction in the pH, SS/TA ratio and industrial index for the two evaluated cultivars. The garlic maintained the ideal pattern for consumption for up to 120 days of storage for both cultivars. The cultivar Roxo Pérola de Caçador had a storage potential that was superior to that of the cultivar BRS Hozan.